Students talk about difficulties they have in solving math problems - Wahyuni, Wahyuni; Zaiyar, M; Mazlan, Mazlan; Saragih, Sahat; Napitupulu, Elvis (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
The ability to solve students' mathematical problems cannot be diagnosed clearly just by using test questions; it must also be seen by looking at students' responses to the problem-solving process. As a result, the purpose of this study is to investigate students' mathematical problem-solving skill as well as their responses to the problem-solving process. This study is descriptive-qualitative in nature. Three junior high schools (SMP) in Aceh participated in this study, with 76 class VIII students serving as research subjects. Tests, observations, and interviews were used as data collection techniques. Quantitative data were descriptively analyzed using proportions, while qualitative data were descriptively analyzed using coding. The results showed that 25 percent of students wrote down what was known and asked, which was an indication of problem comprehension; 21 percent of students were able to devise problem-solving strategies; and 15 percent of students had done calculations correctly. correct, 11 percent of students checked their answers again. Based on the responses given by students, there were some difficulties experienced by students when solving math problems, namely difficulty understanding reading texts, using mathematical terms, making problem connections, making decisions, uncertainty in solving problems, time, carelessness, and boredom. The findings of this study are expected to serve as a resource for teachers and education practitioners in developing focus, discipline, and patience in problem solving and selecting learning models appropriate to the needs of their students.